Comparison surface characteristics and chemical composition of conventional metallic and Nickel-Free brackets - Shintcovsk, Ricardo Lima; Knop, Luegya Amorim Henriques; Gandini Jr, Luiz Gonzaga; Martins, Lidia Parsekian; Pires, Aline Segatto (Sociedade Brasileira de Pesquisa Odontológica - SBPqO, 2015)
This study aims at comparing conventional and nickel-free metal bracket surface characteristics with elemental composition by scanning electron microscopy (SEM), using energy dispersive spectroscopy (EDS). The sample consisted of 40 lower incisor brackets divided into four groups: ABZ = conventional brackets, Kirium Abzil 3M® (n = 10); RL = conventional brackets, Roth Light Morelli® (n = 10); NF = nickel-free brackets, Nickel-Free Morelli® (n = 10); and RM = nickel-free brackets, Roth Max Morelli® (n = 10). Qualitative evaluation of the bracket surface was performed using SEM, whereby surface features were described and compared. The elemental composition was analyzed by EDS. According to surface analysis, groups ABZ and RL showed a homogeneous surface, with better finishing, whereas the surfaces in groups NF and RM were rougher. The chemical components with the highest percentage were Fe, Cr and C. Groups NF and MR showed no nickel in their composition. In conclusion, the bracket surface of the ABZ and RL groups was more homogeneous, with grooves and pores, whereas the surfaces in groups NF and RM showed numerous flaws, cracks, pores and grooves. The chemical composition analysis confirmed that the nickel-free brackets had no Ni in their composition, as confirmed by the manufacturer’s specifications, and were therefore safe to use in patients with a medical history of allergy to this metal.
Keywords: Orthodontic Brackets; Nickel; Hypersensitivity; Microscopy